A resource-based view of social entrepreneurship: how the human capital influences the job creation in the Lebanese market. (16th April 2023) - Kozaily, Diala; Azoury, Nehme
Social entrepreneurship is a hybrid model - a double mission implementation which is easily perceived separately but less simple when combined together. The entrepreneurship resource-based view introduces the resource-based theory into the entrepreneurship topic and discipline. Since the entrepreneurship and social entrepreneurship are closely comparable, in this study, the entrepreneurship resource-based view is introduced to the social entrepreneurship topic. In particular, the human resources, one out of two other resources or capitals - are part of the social entrepreneur personal development. The social entrepreneur capacities could influence the flourishing of the social enterprise, in consequence the job opportunities created in the market. The methodology is designed on a sample of 38-Lebanese social enterprises to find support for our null or alternative hypothesis for each independent variable we are studying. In details, we find that human capital could influence social entrepreneurship capacity of job creation. On one hand, the education level of the social entrepreneur does not have a significant influence on the expectations of the social entrepreneur to create jobs. On the other hand, the professional experience of the social entrepreneur prior to its social enterprise creation affects the social enterprise job creation expectations.